2016
DOI: 10.4000/asp.4804
|View full text |Cite
|
Sign up to set email alerts
|

What can linguistic approaches bring to English for Specific Purposes?

Abstract: France) where he is currently coordinator of the first year Master's in Applied Foreign Languages (Mention LEA) and co-coordinator with Natalie Kübler of a second year Master's in Languages for Specific Purposes, Corpus Linguistics and Translation studies (Master 2 LSCT). He has taught and conducted research in interlinguistics, specialised translation, phraseology, systemic functional grammar and text linguistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 48 publications
0
8
0
2
Order By: Relevance
“…Thus, distortion in translation interferes with the communicative purpose of these texts, which can be defined as accurate and objective presentation of medical research results in order to facilitate their transfer into clinical practice. Besides certain translation errors, which are a rather obvious source of such distortions, biased translation of lexico-grammatical patterns (Gledhill & Kübler, 2016) was also previously determined to be a potential source of distortion in the interpretation of research results. This is particularly the case for structures containing modal markers because of their importance in specialized languages and the high degree of interpretation associated with their translation.…”
mentioning
confidence: 99%
“…Thus, distortion in translation interferes with the communicative purpose of these texts, which can be defined as accurate and objective presentation of medical research results in order to facilitate their transfer into clinical practice. Besides certain translation errors, which are a rather obvious source of such distortions, biased translation of lexico-grammatical patterns (Gledhill & Kübler, 2016) was also previously determined to be a potential source of distortion in the interpretation of research results. This is particularly the case for structures containing modal markers because of their importance in specialized languages and the high degree of interpretation associated with their translation.…”
mentioning
confidence: 99%
“…The focus of this paper is on the translation of lexico-grammatical patterns, i.e., "the basic building blocks" of languages for specific purposes (LSPs) [11] (p. 75). Composed of stable pivotal elements and a more variable albeit regular paradigm, these "chains of meaningful interlocking lexical and grammatical structures" can be extended and are non-linear, and have regular textual functions [11] (p. 79). An example of a typical lexico-grammatical pattern in technical language that functions as a warning would be "FAILURE TO + V [= comply with, follow, observe, etc.]…”
Section: Lexico-grammatical Patterns As a Source Of Distortion In Tramentioning
confidence: 99%
“…+ MAY/CAN + LEAD TO/RESULT IN + N [= death, fire, injury, property damage, etc.]" [11] (p. 78). Within the ongoing PhD project [8], various lexico-grammatical patterns used in Cochrane review abstracts for the communication of specialized medical knowledge have been identified.…”
Section: Lexico-grammatical Patterns As a Source Of Distortion In Tramentioning
confidence: 99%
“…It forms the basis for many of the pedagogical and language-acquisition theories that have developed over the years. The two principal applied-linguistic approaches to ESP are the concept-oriented approach and the context-oriented approach (Gledhill & Kübler, 2016). The concept-oriented approach concentrates on the technical language and linguistic structures employed within a specialist domain, for example through metaphor analysis (English, 1998), whereas the contextoriented approach considers the social or cultural context when analysing specialist language.…”
Section: Literature Reviewmentioning
confidence: 99%